Utility of NKX3.1 immunohistochemistry in the differential diagnosis of seminal vesicles versus prostatic tissue in needle biopsy - Pitra, Tomas; Pivovarcikova, Kristyna; Alaghehbandan, Reza; Compérat, Eva Maria; Hora, Milan; Rogala, Joanna; Slisarenko, Maryna; Michal, Michal; Hes, Ondrej (Annals of diagnostic pathology, 2020)
NKX3.1 is considered a reliable immunohistochemical marker of prostatic origin with high specificity and sensitivity. However, NKX3.1 positivity has been described in other neoplastic and non-neoplastic tissues, such as mesenchymal chondrosarcoma, sex-cord stromal tumors, rete testis adenocarcinoma, lobular and ductal carcinoma of the breast, salivary glands, peribronchial submucosal glands, and Sertoli cells. We analyzed expression of two antibodies (mono and polyclonal) of NKX3.1 in a total of 63 non-neoplastic seminal vesicles. We used 52 resection materials (12 seminal vesicles without prostatic adenocarcinoma, 26 seminal vesicles with prostatic adenocarcinoma infiltration, and 14 cases of seminal vesicles infiltrated by urothelial carcinoma) and 11 prostatic core needle biopsies with incidentally sampled fragment of seminal vesicles. In all cases, tissues from seminal vesicles were completely negative for NKX3.1, despite using polyclonal and monoclonal NKX3.1 antibodies, and regardless of the detection system utilized (diaminobenzidine (DAB) versus alkaline phosphatase (AF)). However, prostatic adenocarcinoma was negative in several cases (n = 6), when AF detection system was used. Reaction with DAB was strong and robust in all cases. Based on our data, we can recommend NKX3.1 as a negative immunohistochemical marker of seminal vesicles.
Keywords: Prostatic Neoplasms; Adenocarcinoma; prostata; nádory prostaty; NKX3.1; semenné váčky; Humans; diferenciální diagnóza; lidé středního věku; Biopsy, Needle; Seminal Vesicles; Transcription Factors; Biomarkers, Tumor; jehlová biopsie; Aged; Diagnosis, Differential; senioři; lidé; Homeodomain Proteins; Immunohistochemistry; imunohistochemie; nádorové biomarkery; Seminal vesicles; Male; Prostate; Middle Aged; Prostatic adenocarcinoma; homeodoménové proteiny; Aged, 80 and over; senioři nad 80 let; adenokarcinom; transkripční faktory; mužské pohlaví